Promotion Pathways of Financial Performance: A Configuration Analysis of Corporate Social Responsibility Based on a Fuzzy Set Qualitative Comparative Analysis Approach - Chunbao Wang; Haiwei Zhou; Yukuo Zhang; Liming Liu (IEEE Access, 2022)
To explore the mechanism of multiple conjunctural causation underlying differences in financial performance, this study selects 39 Chinese companies from the Fortune Global 500 as samples and applies configurational thinking and the qualitative comparative analysis (QCA) approach to integrate five variable conditions concerning corporate social responsibility (CSR). The results show that 3 path configurations achieve high financial performance. Specifically, the first configuration includes highly responsible governance, superior employee rights and interests, and effective environmental protection. The second configuration includes highly responsible governance, superior employee rights, and active public charity. The third configuration includes highly responsible governance, active public charity, and effective environmental protection. The four dimensions involved in the above three path configurations have alternative effects in interpreting financial performance. When the level of responsible governance ability is high, as long as any two conditions among employee rights and interests, environmental protection and public charity also attain a high level, this situation can drive the corporation to achieve high financial performance. Based on the conclusions of this paper, management implications from the perspectives of firms are also proposed.